From Development to Implementation: Usability and Performance Evaluation of an Internship System - Andrian, Dimas Pamilih Epin; Massaty, Muhammad Hassan (Lembaga Yasin AlSys, 2025)
This study aims to develop a web-based internship management system to enhance efficiency, transparency, and usability for students and university administrators. Traditional internship management methods often suffer from inefficiencies and limited accessibility, necessitating a more structured digital approach. By integrating User-Centered Design (UCD) and Feature-Driven Development (FDD), an Agile methodology, this research focuses on improving system usability and user experience. The method involved data collection through interviews with students and university administrators to identify key requirements. The platform was developed iteratively, incorporating continuous feedback to ensure alignment with user needs. Feature prioritization and incremental implementation allowed for a structured approach to system refinement, resulting in a more effective and adaptable solution. The results indicate that the developed platform successfully addresses key challenges in internship tracking, document management, and communication. Usability evaluations using User Experience Quality (UEQ) metrics show high satisfaction in accuracy, efficiency, and clarity, while engagement remains an area for further improvement. This research contributes to digital transformation in internship management, with future potential for AI-driven automation in feedback analysis and internship matching.